In silico investigation of ACE2 and the main protease of SARS-CoV-2 with phytochemicals from Myristica fragrans (Houtt.) for the discovery of a novel COVID-19 drug - Tassanee Ongtanasup; Smith Wanmasae; Siriwan Srisang; Chawan Manaspon; Soiphet Net-anong; Komgrit Eawsakul (Saudi Journal of Biological Sciences, 2022)
compounds have potential as effective medicines to combat the COVID-19 pandemic. However, to assess the therapeutic potential of these ligands, additional research is needed, which will use our findings as a foundation.
Keywords: Piperaceae Chemical and Biological Studies; Drug-Induced Hepatotoxicity and Protection; Cholinesterase and Neurodegenerative Diseases